Work-related Road Traffic Crash: Is Return to Work Rate After Rehabilitation Better With Outcome-focused Intervention? DUPLICATE - Sahak, Nurrul Hafeezah; K.C Mani, Kulanthayan; Hamedon, Titi Rahmawati; Rampal, Krishna Gopal; S. Vythialingam, Kathirkamanathan (2019)
Introduction: Work-related road traffic crashes (RTC) are a significant global public health challenge due to the seriousness of its consequences. Injured workers who have survived work-related RTC are advised to go for rehabilitation after they have been treated physically by healthcare providers. Reintegrate as soon as possible into the working community able avoid long periods of sick leave. Return to work (RTW) rate have been used extensively in many previous studies as an indicator of rehabilitation outcomes on the working capacity of injured workers. The objective of this study was to compare RTW rate after rehabilitation for injured workers who received physical rehabilitation only (control group) and physical rehabilitation plus outcome-focused intervention (intervention group). Methods: Eligible 200 workers who were involved in work-related RTC and agreed to participate in SOCSO RTW Program were identified and invited to be part of this study. Sociodemographic, employment and injury-related questions were distributed. Results: This study finding showed majority (79.5%) of the respondents were aged 25 years old or older, male (86.0%), married or divorced (63.5%), and attained secondary and below education level at secondary or below (66.0%). More than half of injured workers consisted of blue-collar workers (69%), had fracture injury (93.0%), and had injury to their lower limbs (48.5%). RTW rate was higher in the intervention group (received physical rehabilitation and outcome-focused intervention) compared to the control group (received physical rehabilitation only). Conclusion: RTW rate for work-related RTC was higher with outcome-focused intervention, in addition to physical rehabilitation.